Barriers Experienced During Fatherhood and the Role of Adverse Childhood Experiences: A Mixed-Methods Approach - Sravya Gurivireddygari; Samantha Hicks; Elisabeth Hayes; Meera Rao; Sebastian Densley; Sumaita Choudhury; Panagiota Kitsantas; Maria Mejia; Lea Sacca (Societies)
Given the critical role of fatherhood in child development and the significant challenges faced by fathers in underserved communities, there is a pressing need to better understand the specific barriers they encounter. This exploratory mixed-methods study examines the prevalence of adverse childhood experiences (ACEs) among fathers, including English, Spanish, and Creole speakers, and explores how social determinants of health exacerbate these barriers. Quantitative data were collected from June 2022–2023 using REDCap survey software. Additionally, three focus groups were conducted with 18 fathers residing in Palm Beach County (PBC), each group based on the primary language spoken at home. The focus groups were conducted in person via the Healthy Mothers Healthy Babies Coalition (HMHB) outreach team at community centers within the PBC. Stated barriers to fatherhood were thematically classified according into three main themes: (1) limited access to and knowledge of resources in the community; (2) challenges in navigating new roles, resources, and fatherhood responsibilities; and (3) important values in parenting. Over 40% of the fathers reported barriers to being involved in their child’s life. The most frequent barriers included work (35.4%) and lack of transportation distance (12.5%). Bivariate analysis using the fisher’s exact test showed a significant association between scoring greater than 4 on the ACE criteria checklist and experiencing barriers to being involved in the child’s life (p-value = 0.013). Findings from this study aim to inform the development of culturally tailored interventions that address disparities in fatherhood support, ultimately contributing to improved outcomes for both fathers and their children.